MODELS OF URANIUM DISSOLUTION IN NATURAL WATERS OF VARIOUS COMPOSITIONS - Barsukov V.L.; Borisov M.V. (My University, 2003)
Computer simulations were used to clarify some principal problems of the interaction of natural waters of various types with natural and anthropogenic U-bearing phases U(cr), UO2(cr), U 4O9(cr), U3O8(cr), UO 2(OH)2(cr), and UO3(cr), in a thermodynamically closed system. The problems discussed include the solubilities of these phases, modes of U occurrence in waters in equilibrium with each of the solid phases, transformations of the solid U-bearing phases in contact with waters, and the alterations in the waters themselves in contact with the U-bearing phases. The effect of external factors that are able to change the physicochemical conditions in the contact of U with waters on these processes is elucidated. The factors encompass differences in the R/W ratios, drastic changes in pH and Eh due to the simultaneous dissolution of U and other anthropogenic products, and the heating of the reaction zone.